2013
DOI: 10.1182/blood-2012-09-457135
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant facilitates tolerance induction to factor VIII in hemophilic mice through a Foxp3-independent mechanism that relies on IL-10

Abstract: Key Points An adjuvant (alum), known to boost immune responses, can be used to facilitate a tolerogenic protocol. Nondepleting anti-CD4 can lead to Foxp3+ regulatory T-cell–independent tolerance that relies on IL-10.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 47 publications
2
12
0
Order By: Relevance
“…By the use of constitutive Treg-deficient sf mice which develop autoimmunity without exogenous manipulation, we were able to examine Foxp3 þ Treg-independent anti-CD4-induced tolerance in isolation. Our results are in line with a recent study showing that anti-CD4 induces tolerance to factor VIII in a Foxp3-independent fashion [40]. However, whereas tolerance to factor VIII was dependent on IL-10 [40], we found no increased IL-10 expression by tolerized CD4 þ T cells and actually reduced IL-10 levels in the serum of tolerized sf mice.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…By the use of constitutive Treg-deficient sf mice which develop autoimmunity without exogenous manipulation, we were able to examine Foxp3 þ Treg-independent anti-CD4-induced tolerance in isolation. Our results are in line with a recent study showing that anti-CD4 induces tolerance to factor VIII in a Foxp3-independent fashion [40]. However, whereas tolerance to factor VIII was dependent on IL-10 [40], we found no increased IL-10 expression by tolerized CD4 þ T cells and actually reduced IL-10 levels in the serum of tolerized sf mice.…”
Section: Discussionsupporting
confidence: 94%
“…Our results are in line with a recent study showing that anti-CD4 induces tolerance to factor VIII in a Foxp3-independent fashion [40]. However, whereas tolerance to factor VIII was dependent on IL-10 [40], we found no increased IL-10 expression by tolerized CD4 þ T cells and actually reduced IL-10 levels in the serum of tolerized sf mice. Supporting our findings, we report that Treg-indpendent tolerance is recessive and noninfectious.…”
Section: Discussionsupporting
confidence: 94%
“…Data from a Phase 1 clinical trial showed that TRX1 was well tolerated and did not deplete T cells [24]. Proposed mechanisms of action of non-depleting anti-CD4 include down-modulation of the CD4 receptor on T cells, and induction of regulatory T-cells [25], [26], [27]. In this study we showed that a short-course treatment with an anti-CD4 mAb successfully induced long-term ERT-specific immune tolerance in Pompe disease mice, implying that this may prove a favorable prophylactic ITI protocol for infants.…”
Section: Discussionmentioning
confidence: 99%
“…4 Although there are currently no prophylactic protocols against inhibitor formation in patients, preclinical experiments in murine models of hemophilia A have provided proof of principle that preventive immune tolerance to FVIII can be established. [6][7][8][9][10][11] However, such protocols use genetic manipulation or immune suppressive drugs, raising safety concerns for translation to human treatment. In contrast, oral tolerance could be a more readily acceptable form of prophylactic tolerance induction and may be more readily tested in clinical trials.…”
Section: Introductionmentioning
confidence: 99%